Penyembah-Penyembah Benar Menurut Yohanes 4:23: Kaitannya Terhadap Pengenalan Akan Allah - Didit Yuliantono Adi; Endik Firmansah (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This scientific study aims to explore the meaning of true worship according to John 4:23 and its relation to knowing God. True worship must be grounded in the three essential aspects of the Christian faith: orthodoxy (right doctrine), orthopraxy (right practice), and ortholatry (right worship). The truth in this context is not philosophical or anthropocentric but Christocentric, with Scripture as its ultimate standard. God is both the foundation and the ultimate goal of all Christian reality. As the Creator, He sovereignly rules over all of life. He alone is worthy of worship and glorification. Scripture explicitly describes worshiping God as being conducted "in spirit and truth." Since God is Spirit, worship must be a spiritual communion with Him. Moreover, God has revealed Himself through His Word, which is now inscripturated in the Bible and must be understood through a biblical-theological framework. Using a qualitative research method with a literature study approach, this study seeks to explore the meaning of true worship in John 4:23 to obtain theologically sound and accountable findings. The author argues that the biblical concept of true worship in John 4:23 provides a theological foundation for the congregation to grow in knowing God through a life of genuine spiritual devotion. This study provides a fresh perspective, highlighting that the practice of authentic worship holds a vital role in the knowledge of God.